A Four Element-Themed Self-Selecting Mobile Application for ESP Testing - Laythe, Brian Robert; Roberts, Natalie (Journal of Scientific Exploration, 2023)
The current study engaged in a pilot data analysis for the purpose of examining a newly developed E (Element)-PSI application which was completed in varying real life environments while reporting information about their location, mood, and focus on the ESP task. In addition, participants completed an ESP induction task, and trait measures of Transliminality, Paranormal Belief, and paranormal experience as measured by the Survey of Strange Events. A total of 44 participants from the United States completed the study as part of an initial registration process for an ongoing experiment. Results indicate small, but non-significant effects due to sample size in terms of the induction process and focus on the ESP task towards positive increases in ESP hit rates. Implications from this research in terms of cultural, trait, and contextual variables contributing to ESP success rates are discussed in terms of using these findings towards formal large sample replication.